Effects of a sub-minimum inhibitory concentration of chlorhexidine gluconate on the development of in vitro multi-species biofilms. Issue 2 (7th February 2020) - Suzuki, Yuki; Ohsumi, Tatsuya; Isono, Toshihito; Nagata, Ryoko; Hasegawa, Taisuke; Takenaka, Shoji; Terao, Yutaka; Noiri, Yuichiro
Abstract: Following antimicrobial administrations in oral environments, bacteria become exposed to a sub-minimum inhibitory concentration (sub-MIC), which can induce in vitro single-species biofilms. This study explored the effects of chlorhexidine gluconate (CHG) at a sub-MIC on in vitro multi-species biofilms comprising Streptococcus mutans, Streptococcus oralis and Actinomyces naeslundii . CHG at a sub-MIC was found to induce in vitro biofilm growth, although the bacterial growth was not significantly different from that in the control. The gene transcription related to S. mutans multi-species biofilm formation with CHG at a sub-MIC was significantly higher than that of the control, but this was not found in S. mutans single-species biofilms. The bio-volume of extracellular polysaccharides with CHG at a sub-MIC was significantly higher than that of the control. This suggests that CHG at a sub-MIC may promote the development of multi-species biofilms by affecting the gene transcription related to S. mutans biofilm formation.